PERAN PRODUCTION ASSISTANT di CAHAYA HATI INDONESIA INEWS - Dika Sandika (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2020)
The purpose of this study is to reveal the role of Production Assistant in the Cahaya Hati Indonesia program on iNews. This program airs every Saturday and Sunday at 12.00 - 13.30 WIB. A talkshow program that presents speakers or lecturers to provide information and deepen the religious community. To create an event program, it takes good cooperation from each production team, one of which plays a role in the production team is the Production Assistant. To analyze the results of the study, researchers used the concept of Production Assistant which consisted of Setting Up, The Fine Details, Schedules and Running Orders, The Script, Timing, Counting and Stopwatches, and Post Production. Researchers used a qualitative approach, with a type of descriptive research. Data collection techniques used observation and in-depth interviews. The results of research conducted indicate that there are statements that are not in accordance with the concept. But key informant and informant statements still make sense and are logical. The practical benefits of this research are expected to be an input for iNews TV in general and the Production Assistant of the Cahaya Hati Indonesia iNews team in particular and the academic benefits of this research to contribute knowledge for the development of communication science, particularly in the broadcasting field and as a reference material for students' libraries communication science, especially students to add insight, especially about the role of Production Assistant. The conclusion of this research is about the role of Production Assistant starting from the pre-production, production and post-production processes.